Characterization of a hybrid femtosecond system based on a photochemically driven XeF(C-A) active medium; Abstracts of the IXth International Conference Atomic and Molecular pulsed lasers, Tomsk, september 14-18, 2009 - Aristov A.; Grudtsin Ya.; Ivanov N.; Krokhin O.; Losev V.; Mamaev S.; Mesyats G. A. Gennady Andreyevich; Mikheev L.; Panchenko Yu.; Rastvortseva A.; Ratakhin N.; Sentis M.; et al. (2009, 2009)
В фонде НТБ ТПУ отсутствует